PENATALAKSANAAN PADA WANITA 70 TAHUN DENGAN KATARAK MELALUI PENDEKATAN KEDOKTERAN KELUARGA - Sindi Yulia Mustika (LPPM Sekolah Tinggi Ilmu Kesehatan Siti Hajar Medan, 2022)
Background: Cataract is a cause of blindness that covers approximately half of all blindness in developing countries. There is an increase in new cataract patients about 2 million every year. Objective: Implementation of family doctor services based on evidence based medicine by identifying risk factors, clinical problems, management and prevention in patients based on a patient problem solving framework with a patient centered, family approach and community oriented approach. Methods: The analysis of this study is a case report. Primary data were obtained through autoanamnesis and alloanamnesis, physical examination and home visits. Assessment is carried out based on a holistic diagnosis from the beginning, process, and end of the study qualitatively. Results: A 70-year-old patient came because of cloudy vision in both eyes. Eye localis status: The right eye lens is cloudy shadow test(+) with 6/20 vision, and the left eye lens is cloudy shadow test(+) with 6/15 vision. The patient's knowledge about the disease is lacking, does not know the risk factors and does not know that surgery is the right choice for cataracts. In the knowledge assessment, the score before the intervention was 4 (low) and after the intervention was 7 (high). In the behavioral aspect, the patient has registered for cataract surgery. Conclusion: After a holistic and comprehensive management was carried out, the patient and family experienced an increase in knowledge about the disease suffered by the patient and had registered for cataract surgery